2003
DOI: 10.1097/01.ccm.0000084807.15352.93
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated pneumonia after heart surgery: A prospective analysis and the value of surveillance*

Abstract: Patients undergoing heart surgery have a high frequency of VAP. VAP is associated with a poor prognosis. In this study, surveillance cultures failed as an anticipative diagnostic method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
96
3
11

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 47 publications
7
96
3
11
Order By: Relevance
“…Overall in-hospital mortality in the study population was 6.9%, with a mortality rate in patients with VAP of 45.7% vs 2.8% in patients without VAP (P ≤ .001). However, in a recent European multicenter study [40], a VAP incidence rate of 2.2%, lower than that found in our and other studies [3,38,39], was identified.…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…Overall in-hospital mortality in the study population was 6.9%, with a mortality rate in patients with VAP of 45.7% vs 2.8% in patients without VAP (P ≤ .001). However, in a recent European multicenter study [40], a VAP incidence rate of 2.2%, lower than that found in our and other studies [3,38,39], was identified.…”
Section: Discussioncontrasting
confidence: 48%
“…Mortality in patients with VAP is a controversial subject concerning patients admitted to the ICU because the target population is severely ill and the level of associated mortality is high. Several studies have attempted to clarify the issue [3,15,16]. Bueno-Cavanillas et al [15] found that critically ill patients with a nosocomial infection, mainly bacteremia and pneumonia, have a higher rate of mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations